A double-blinded prospective randomized control study of preoperative administration of intravenous mephentermine vs intramuscular mephentermine in preventing post-spinal hypotension in caesarean section - Sagnik Datta; Suman Chattopadhyay; Arun K Mandi; Debasish Bhar (Journal of Obstetric Anaesthesia and Critical Care, 2024)
Context: Mephentermine by intramuscular route prevents post-spinal anesthesia hypotension. However, the intravenous route had not been tried earlier for this prophylactic purpose. Aims: Comparing the safety and efficacy of intravenous and intramuscular routes of mephentermine in preventing maternal hypotension during cesarean section (CS). The primary objective was to compare the incidences of hypotension. Methods and Material: ASA II term parturients posted for CS were randomized into three groups. Group I received intravenous mephentermine 10 mg just before spinal and 1 ml normal saline (NS) by intramuscular route 10 minutes before spinal. Group M received intramuscular mephentermine 15 mg 10 minutes before spinal and 1 ml NS by the intravenous route just before spinal. Group C received 1 ml NS intramuscularly 10 minutes before spinal and 1 ml NS by the intravenous route just before spinal. The vital parameters, episodes of hypotension, adverse events, and neonatal parameters were assessed. Results: During midterm analysis, it was found that Group I had significantly higher adverse effects, so data collection was stopped, with a total intake of 25 patients in Group M, 22 patients in Group I, and 20 patients in Group C, respectively. The incidence of hypotension was less with the use of IM (8%) and IV (22.7%) mephentermine compared to the control group (P value: <0.05). Group I had significantly more adverse events like headache (59%), chest pain (36.36%), and ST changes compared to other groups (P value: <0.001). Conclusions: We conclude that the intramuscular route is better for preventing post-spinal hypotension in cesarean section with lesser maternal side effects and a better Apgar score.